Application of Data Mining Using Multiple Linear Regression to Project Population Figures at the Central Bureau of Statistics of Ogan Ilir Regency - Meiky Alfarizi (Institute of Information Technology and Social Science (IITSS), 2025)
The Central Bureau of Statistics (Badan Pusat Statistik BPS) is a government agency mandated to provide comprehensive, accurate, and up-to-date population statistics to build a reliable, effective, and efficient national statistical system that supports national development planning. However, the BPS office of Ogan Ilir Regency faces challenges in its current population-data collection system, which remains incomplete. This study applies a multiple linear regression analysis method a multivariate technique used to estimate the relationships between dependent and independent variables of metric or non-metric type. The findings demonstrate that data-mining techniques are effective tools for addressing data-related problems by identifying useful and relevant knowledge within large databases. The proposed projection information system is designed to meet population-data requirements at the regency or municipal level for both present and future needs.